STRATEGI PENYALURAN BEASISWA PENDIDIKAN DI LAZISMU BANTUL KOTA - Riandara , Fatur Roza; Suyatno, Suyatno (Jurnal Progress Administrasi Publik, 2025)
Education is an effort to develop skills and optimize the potential that exists in a person to improve the quality of Human Resources (HR). Based on the Constitution, Article 31 Paragraph 1 and Paragraph 2, every individual has the right to receive education and is obliged to follow basic education, while the government is obliged to provide scholarship assistance for poor or underprivileged families. The method used in this study is qualitative, with data collection techniques including observation, interviews, documentation. The data analysis techniques used are data reduction, data analysis, and drawing conclusion. The purpose of this study is to analyze the scholarship distribution strategy, inhibiting and supporting factors and provide suggestions in conducting data collection. The results of this study indicated that Lazismu Bantul City strategy in distributing scholarships began the process by registering prospective recipients from AUM SD and SMP in PCM (Muhammadiyah branch leadership) Bantul, as well as collecting information from PRA and the community. However, the implementation of scholarship distribution had experienced obstacles, which has caused the distribution to be less effective.   Keywords: Distribution; Education; Strategy; Scholarships